Association of body mass index with non-achievement of target low-density lipoprotein level in older patients at very high cardiovascular risk: a multicentre study. (14th October 2021) - Nguyen, H T; Nguyen, A H; Lam, H M; Nguyen, T T
Abstract: Introduction: Low-density lipoprotein cholesterol (LDL-c) is a well-established risk factor for atherosclerotic cardiovascular disease. Nonetheless, the association of body mass index (BMI) with non-achievement of target LDL-c level in older patients with type 2 diabetes (T2D) at very high cardiovascular risk is unknown. Purpose: To investigate whether BMI is associated with non-achievement of target LDL-c level in older patients with T2D at very high cardiovascular risk. Methods: From December 2019 to June 2020, in this multicentre prospective cross-sectional study, we enrolled 733 consecutive outpatients aged ≥60 years with T2D at very high cardiovascular risk in whom LDL-c levels could be measured after any stable lipid-lowering therapy for ≥6 months. Achievement of target lipid level was assessed based on the 2019 guidelines of the European Society of Cardiology for dyslipidaemia. Factors associated with non-achievement of target LDL-c level were determined using logistic regression analysis. Results: Of the total cases (age, 68.6±7.2 years; men, 51.3%), 654 patients (89.2%) did not achieve an aggressive target LDL-c level of <1.4 mmol/L. Target non-high-density lipoprotein cholesterol level of <2.2 mmol/L and triglyceride level of <1.7 mmol/L were not achieved in 87.9% and 56.2% of the patients, respectively. In the multivariate model, BMI was the only factor associated with failure to achieve target LDL-c level, but not other factors such as age, sex, education level, smoking, and comorbidities. The adjusted odds ratio were 0.88 (95% confidence interval [95% CI], 0.24–3.21; P=0.84) for underweight, 1.57 (95% CI, 0.87–2.81; P=0.13) for overweight, and 2.63 (95% CI, 1.43–4.83; P=0.002) for obesity (normal weight was set as reference) status. Conclusions: Non-achievement of target LDL-c level is highly prevalent in older patients with T2D at very high cardiovascular risk. Obesity, defined by BMI, can be a factor associated with non-achievement of the target. The findings highlight the importance of management of lipid levels in older patients with T2D. FUNDunding Acknowledgement: Type of funding sources: None.